2008
DOI: 10.1196/annals.1432.045
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Nicotine and/or Cocaine Differentially Alters Nicotine‐Induced Sensitization in Aging Offspring

Abstract: Repeated exposure to psychostimulant drugs can result in behavioral sensitization, an amplified response in locomotor activity and stereotypy, which is used to model aspects of drug addiction. The expression of behavioral sensitization, induced by i.p. injections of nicotine once daily for 5 days, was examined in 450-day-old male rats exposed prenatally on GD 8-20 to one of the following conditions: (1) low nicotine: 2.5 mg/kg/day nicotine [LN]; (2) high nicotine: 5.0 mg/kg/day nicotine [HN]; (3) low nicotine/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Four studies report a blunting of the excitatory effect of nicotine challenge on activity due to low doses of prenatal nicotine exposure (Ankarberg et al 2001(Ankarberg et al , 2004Sobrian et al 2008), and two others report the opposite effects after high doses of prenatal exposure (Shacka et al 1997;Sobrian et al 2008). Interestingly, these studies either used only males (Ankarberg et al 2001(Ankarberg et al , 2004Eriksson et al 2000;Sobrian et al 2008) or found such effects in males but not females (Shacka et al 1997).…”
Section: Response To Drug Challengementioning
confidence: 88%
See 4 more Smart Citations
“…Four studies report a blunting of the excitatory effect of nicotine challenge on activity due to low doses of prenatal nicotine exposure (Ankarberg et al 2001(Ankarberg et al , 2004Sobrian et al 2008), and two others report the opposite effects after high doses of prenatal exposure (Shacka et al 1997;Sobrian et al 2008). Interestingly, these studies either used only males (Ankarberg et al 2001(Ankarberg et al , 2004Eriksson et al 2000;Sobrian et al 2008) or found such effects in males but not females (Shacka et al 1997).…”
Section: Response To Drug Challengementioning
confidence: 88%
“…It should also be noted that these drug challenge studies were conducted mostly in adults; only one tested neonates (Shacka et al 1997), four tested adolescents (Abreu-Villaça et al 2004a; Pauly et al 2004;Seidler et al 1992, and eight tested adults (>PND 70; Ankarberg et al 2001Ankarberg et al , 2004Chistyakov et al 2010;Eriksson et al 2000;Fredriksson et al 2000;Sobrian et al 2003Sobrian et al , 2008Zbuzek and Chin 1994).…”
Section: Response To Drug Challengementioning
confidence: 97%
See 3 more Smart Citations